The Cultural “Blood Ties” Between Medical Anthropology and Cardiovascular Disease: A Narrative Review - Davide Costa; Raffaele Serra (Societies)
Background: Medical anthropology is a subfield that examines the various factors influencing health, disease, illness, and sickness. Cardiovascular disease (CVD) encompasses a range of disorders affecting the heart, arteries, and veins. Patients with CVD face significant, unique health challenges, including functional decline, repeated hospitalizations, and psychological and social issues, which contribute to a global decline in health and escalate health system costs. Medical anthropologists have explored this extensive category of diseases in numerous ways, including cross-cultural studies that enhance our understanding of these conditions. Therefore, building on these preliminary insights, this article posed the following research question: How does medical anthropology enhance our understanding, prevention, and management of cardiovascular diseases through cultural, social, and behavioral lenses? Methods: This study examined the research question through a narrative literature review. Results: The literature analysis revealed connections between medical anthropology and specific CVDs: heart disease, hypertension, arterial disease, venous disease, and wound care. Conclusions: The findings from the literature analysis indicate what could be described as the cultural “blood ties” between medical anthropology and cardiovascular disease. In this manner, in the spirit of integration, inter-, and transdisciplinarity, it is increasingly necessary to incorporate mixed-method approaches drawing from both the anthropological and medical fields to better deliver tailored care.